2020
DOI: 10.1088/1755-1315/564/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Water quality study and pollution index based on Physics-chemical parameters in the Youtefa Bay tourism area, Jayapura

Abstract: Good water quality is extremely important to support the life of the organism. The determination of water quality status was needed as a reference to monitor water pollution. This study aimed to assess the status of water quality and determine the pollution index based on physical-chemical parameters in the Youtefa bay tourism area. Sampling was carried out in august 2019 across six research stations; then, the result was compared with water quality standard based on KEPMEN-LH No. 51 the Year 2004 For marine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Based on observation results, the water quality in Youtefa Bay was still in good condition for the life of biota, as seen from the transparency level of 0.7-5 m (Table 3). This value is higher than Sari et al (2021), which found that the transparency level in the area of Tobati, Enggros and Nafri ranged from 0.6 to 2.8 m. The level is good according to the standards for biota according to the Minister of Environment Decree Number 51 of 2004 at <5 m. Garbages found in the waters of the studied area were plastic, drink bottles, building materials, and residual oil from industrial and ship waste disposal. These cause unpleasant odor that reduces the aesthetic value of tourism sites in Youtefa Bay.…”
Section: Water Quality Parametersmentioning
confidence: 64%
See 1 more Smart Citation
“…Based on observation results, the water quality in Youtefa Bay was still in good condition for the life of biota, as seen from the transparency level of 0.7-5 m (Table 3). This value is higher than Sari et al (2021), which found that the transparency level in the area of Tobati, Enggros and Nafri ranged from 0.6 to 2.8 m. The level is good according to the standards for biota according to the Minister of Environment Decree Number 51 of 2004 at <5 m. Garbages found in the waters of the studied area were plastic, drink bottles, building materials, and residual oil from industrial and ship waste disposal. These cause unpleasant odor that reduces the aesthetic value of tourism sites in Youtefa Bay.…”
Section: Water Quality Parametersmentioning
confidence: 64%
“…The value obtained at each data collection station indicated the waters are in very good condition. Sari et al (2021) also reported that the pollution index value shows that the waters in Tobati Village and Youtefa Bay Pier are suitable for marine life.…”
Section: Water Quality Parametersmentioning
confidence: 96%
“…According to Silaen and Mulya (2018) the high value of BOD5 indicates the number of organic matter compounds that enter the water. The BOD5 parameter is one of the parameters to determine the level of water pollution, if the BOD5 value is higher than the quality standard, then the water is said to be polluted, and vice versa if the BOD5 value is lower, then the water pollution level is low (Sari et al 2020). Salinity values at each station range from 17.5-250/00.…”
Section: Discussionmentioning
confidence: 99%
“…The value of this anomia range is suitable for the life of the mud crab. According to Sari et al (2020), the seawater quality standard for NH 3 is 0.3 ppm for marine biota. According to Karim (2013;Ganesh et al, 2015), mud crabs can grow well, at concentrations of ammonia in the media not more than 0.1 ppm Nitrite (NO 2 ) for aquatic organisms, including crabs directly, nitrite is a type of toxic material, usually formed in intensive cultivation or polluted waters (Ramdhani et al, 2013;Weihrauch et al, 2018;Rochmah and Mangkoedihardjo, 2019).…”
Section: Discussionmentioning
confidence: 99%